إطار مقترح للإفصاحات غير المالية لتقارير الأعمال المتكاملة وفقاً لاحتياجات أصحاب المصالح في ليبيا دراسة استكشافية على فئات متعددة لأصحاب المصالح في ليبيا - الفضلي , خالد زيدان; العريبي , خالد عبد القادر; بن مراد , فاطمة وئام (Scientific Journal of University of Benghazi, 2022)
The study aimed to formulate a proposed model for non-financial disclosures for integrated business reports, according to the needs of stakeholders in Libya, to achieve the goal of the study. The descriptive approach was adopted as a research method; This approach is ideal for understanding the different aspects of the problem under study. The study also collected its data through a list of questionnaires addressed to several categories of stakeholders in the Libyan business environment, represented by commercial banks, investors, financial analysts, and external auditors. The study concluded that the proposed disclosure requirements for non-financial information for integrated business reports were accepted by the majority of stakeholders; Where the degree of acceptance of non-financial disclosures for risks was 100%, followed by disclosures of non-financial information related to information about the company, including its management and strategy, by 91.6%, and non-financial disclosures related to governance information came in the third rank with 55.5%, followed by disclosures in the fourth rank. Non-financial information related to social information came in at 44.4%, and disclosures about non-financial information related to environmental information came in last place with a rate of 40%. The study also found that there was no difference in the degree of acceptance among all categories of stakeholders for the proposed disclosures of non-financial information for integrated business reports. Since 33 disclosures were accepted and 16 were rejected, However, this does not mean that they are unimportant; Rather, this is due to the lack of knowledge of it in Libyan accounting practice, especially since the disclosures related to governance, environmental and social disclosures have weakness in knowing their importance, and insufficient awareness of them by stakeholders in the Libyan environment. Finally, the study made several recommendations, the most important of which is the necessity of issuing a special standard for integrated business reports to suit the economic, social, and environmental conditions in Libya, taking into account the experiences of previous countries that obligated their organizations to integrated business reports. The study also recommended conducting more research in this field using methodologies other; It may contribute to increasing knowledge on this topic.